Closure of Oroantral Communication Utilising Buccal Fat Pad without Removing the Implants in Maxillary Sinusitis: A Case Report of Two Cases - Noriaki Aoki; Megumi Matsumoto; Junichi Baba; Soichiro Ishii; Hiroshi Ozawa (Journal of Clinical and Diagnostic Research)
Although the sinus lift procedure is relatively safe and well-known for bone augmentation in implant cases, it can occasionally lead to acute and chronic postoperative sinusitis as a complication. Generally, treatment for such complications should involve implant removal and Endoscopic Sinus Surgery (ESS). Two cases with similar complications of sinusitis following a sinus lift were reported in the Department of Oral Surgery, where they were managed with different surgical approaches, excluding implant removal and ESS, which is the standard surgical procedure. In the first case, a 50-year-old male with missing teeth and atrophic alveolar bone underwent a sinus lift, bone grafting, and implant placement. One month post-surgery, he developed chronic sinusitis, leading to persistent symptoms. Similarly, another case involved a 48-year-old man who visited the Department of Oral Surgery with a chief complaint of purulent discharge from his nose. In both cases, after clinical and radiological investigations, a final diagnosis of maxillary sinusitis was made, resulting from complications following the sinus lift and implant procedure. The Buccal Fat Pad (BFP) was successfully used to close the Oroantral Communication (OAC) without the need for implant removal or ESS. No infections were clinically or radiographically observed at six months, 12 months, and 24 months postoperatively, and the recovery course was uneventful without any complications. At the two-year follow-up, the patients expressed satisfaction with the results of the implant treatment, demonstrating appropriate implant stability.